Advances in reliability and risk analyses of slopes in spatially variable soils: A state-of-the-art review. (January 2022) - Jiang, Shui-Hua; Huang, Jinsong; Griffiths, D.V.; Deng, Zhi-Ping
Abstract: Spatial variability of soil properties was rarely taken into account directly in traditional slope stability analyses, rather some "average" or suitably "pessimistic" properties are assumed to act across the whole region of interest. In the last two decades, a large portion of published research papers on slope stability have tried to explicitly model the spatial variability of soil properties. In the first decade, research mainly focused on showing the importance of modeling the spatial variability directly in probabilistic slope stability analysis. In the last decade, a rapid development was observed including quantitative risk assessment of slope failure, improving computational efficiency, and directly using site investigation and field monitoring data. This review tries to summarize these advances in the hope that future research directions can be identified.